Peran Manajemen Pendidikan Berbasis Kearifan Lokal dalam Membentuk Karakter Peserta Didik di Era Globalisasi - Ahmad Jauhari Hamid Ripki; Arifannisa Arifannisa (Journal on Education, 2025)
Globalization has brought significant challenges in preserving cultural identity and shaping student character. This study aims to examine the role of local wisdom-based educational management in shaping student character in the era of globalization. The method used is a literature review with a qualitative approach, where data is obtained from 25 articles selected from an initial 50 articles found on Google Scholar between 2007 and 2024. Descriptive analysis is used to identify patterns and main themes from the relevant literature. The findings show that integrating local wisdom into education, such as through cultural arts, oral traditions, and local philosophy, can build student character that is moral, creative, and has a strong cultural identity. Case studies from various regions in Indonesia, such as Bali, Yogyakarta, and Papua, demonstrate the effectiveness of this approach in supporting character development while enhancing student competitiveness. This study suggests the importance of flexible policies, teacher training, and collaboration between schools, government, and communities to support the sustainable implementation of local wisdom-based education